Plasma Levels of α-Synuclein, Aβ-40 and T-tau as Biomarkers to Predict Cognitive Impairment in Parkinson’s Disease - Chen, Nai-Ching; Chen, Hsiu-Ling; Li, Shau-Hsuan; Chang, Yen-Hsiang; Chen, Meng-Hsiang; Tsai, Nai-Wen; Yu, Chiun-Chieh; Yang, Shieh-Yueh; Lu, Cheng-Hsien; Lin, Wei-Che (Frontiers in Aging Neuroscience, 2020)
Objective In this study, we assessed plasma biomarkers to identify cognitive impairment in patients with Parkinson’s disease (PD) by using ultra-sensitive immunomagnetic reduction-based immunoassay (IMR). Methods The study enrolled 60 PD patients and 28 age- and sex-matched normal controls. Participants received complete cognitive function assessments using the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating. PD patients with an MMSE score of < 28 were defined as having cognitive impairment. Meanwhile, a 99mTc-TRODAT-1 scan was performed and plasma levels of Aβ-40, Aβ-42, T-tau, and α-synuclein were evaluated using IMR, subsequent correlation analyses were then performed. Results Compared with normal adults, PD patients have higher plasma levels of α-synuclein and T-tau, and a lower level of Aβ-40 (p<0.05). Plasma levels of α-synuclein (r = -0.323, p=0.002), Aβ-40 (r = 0.276, p=0.01), and T-tau (r = -0.322, p=0.002) are significantly correlated with MMSE scores. The TRODAT scan results, including visual inspection and quantification, revealed significant correlations between Aβ-40 and PD. Multiple regression analysis showed that the plasma levels of Aβ-40 (OR=0.874, 95% CI=0.796 - 0.959) and α-synuclein (OR=1.682, 95% CI=1.017 - 2.782) were independently associated with PD patients with cognitive impairment. The cutoff values for predicting cognitive deficits in PD patients were 45.101 pg/ml of Aβ-40, (Area under curve (AUR) = 0.791), and 0.389 pg/ml of α-synuclein, (AUR = 0.790). Conclusion Plasma levels of α-synuclein and Aβ-40 are potential biomarkers for the detection of cognitive impairment in PD patients.